Building expertise: Identifying policy gaps and new ideas in housing eco-renovation in the UK and France - Fawcett, T; Killip, G; Janda, K (European Council for an Energy Efficient Economy, 2013)
In order to meet national carbon and energy savings targets in both the UK and France, the housing stock needs to be renovated to a high standard of energy efficiency. However, current levels of activity are nowhere near sufficient to meet 2050 targets. The aim of this paper is to identify the policy gaps regarding eco-renovation in the UK and France, and to highlight some promising ideas which could successfully fill those gaps. First, different definitions of eco-renovation are presented, and these aspirational standards are compared with current policy goals. Then a brief description of housing and energy use in each country provides useful background information, and similarities and differences between the countries are identified. Summaries and comparisons of current policy are presented. The mechanisms the policy instruments aim to use to effect change are compared with what is known about ‘barriers’ to eco-renovation. Most policy focuses on reducing the cost to householders, much less is done to address other reasons for inaction such as lack of information, motivation or trust in professionals. Multiple gaps in current policy are identified, including lack of a roadmap to reach 2050 targets, lack of policy tackling non-financial barriers to action, and insufficient policy working with the building industry and other professionals. Case studies of a number of innovations in information provision and delivering eco-renovation are briefly presented. New policy ideas around eco-renovation are discussed, particularly ‘over time’ eco-renovation. These new business and social enterprise innovations and policy ideas could help filling in some policy gaps, but more remains to be done to achieve the very challenging task of renovating the whole housing stock to a high standard.